KONSTRUKSI IDENTITAS SOSIAL GENERASI Z MELALUI INTERAKSI DENGAN CHATGPT - Salim, Salim; Rahmadiana, Rahmadiana; Zibran, Rifaldi; Fajriah, Nurul (Mediakom : Jurnal Ilmu Komunikasi, 2025)
The research aims to understand how the construction of Generation Z's social identity is formed through the process of intrapersonal communication when using ChatGPT as a medium of self-expression or virtual venting. The descriptive qualitative approach is an approach used in research with the constructivist paradigm.  This study explored the subjective experiences of six purposively selected Gen Z informants. The results of the study show that ChatGPT acts as a neutral reflective space for Generation Z.   Generation Z interprets ChatGPT not just as a technological tool, but as a symbolic space that is safe, neutral, and supports self-reflection. The three main themes identified are: a safe space without judgment, privacy and control over personal information, and the free exploration of identity. Interaction with ChatGPT is a means of intrapersonal communication that helps Gen Z manage emotions, understand themselves, and form social identities authentically without social pressure. In this context, ChatGPT acts as a dialogue partner that supports emotional well-being and the search for self-meaning in the midst of the complexity of digital culture.